Peran Media Komunikasi RRI Dalam Meningkatkan Kepedulian Lingkungan Pada Masyarakat Di Kabupaten Biak Numfor Provinsi Papua - Christian Tarandung; Henny Tumbelaka; Imaculata Lamonge; Marthen Tombeg; Fanhaselt Rumbewas (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Radio Communications Media of the Republic of Indonesia (RRI) Aims to: Objectives 1) To find out the role of one of the communication media, in this case Radio Republik Indonesia (RRI) Biak, which is used as a means of information presented by Radio in the form of news events, information and environmental education to the community through non-formal channels. 2) To find out the responses given by the community regarding radio programs/broadcasts related to the environment. Subjective Objectives to fulfill one of the requirements in completing a bachelor's degree at the North Sulawesi University of Technology. To find out the expectations and experiences of the listeners of RRI Biak, the data collection technique in this study was the data triangulation method. Document analysis is carried out before respondents or informants, direct interviews will be conducted with respondents or informants along with direct observations in the field. The data analysis used in this research is using qualitative analysis. Data analysis is a process in which the data is simplified into a form that is easier to read and interpret. This research was also conducted in the Biak Numfor City area of ​​RRI Biak, with the criteria of the respondents being radio broadcast listeners. Based on the results of interviews with several respondents or informants, it can be concluded several things as follows: RRI can be a bridge or link of information to the community regarding an event or events that occur.